The impact of ACLS training in theoretical knowledge - Stirparo, Giuseppe; Gambolò, Luca; Bellini, Lorenzo; Sarli, Leopoldo; Signorelli, Carlo; Ristagno, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Italy has a public health system where also young physicians hold various jobs, including Emergency Services. Advanced Cardiovascular Life Support (ACLS) course is developed for the management of cardiovascular emergencies. This study evaluates the preparation of Italian physicians on ACLS and their perceived need to be trained on it.Methods: surveys had been administered to 4698 Medical Doctors. They consisted of questions on sociodemographic characteristics, knowledge of ACLS protocol, and willingness to attend an ACLS course.Results: Online survey reached 4698 physicians, 137 of them had been excluded for invalid answering. People who had attended an ACLS course scored significantly higher on the test (M=5.68 SD=1.89) than those who had not (M=4.71 SD=1.91). Experienced physicians scored significantly higher (M=5.25 SD=1.96) than recently licensed ones (M=4.84 SD=1.94). Multiple regression was used to predict the ACLS test score.Conclusions: ACLS training has a stronger effect on Cardiovascular Emergency management knowledge (d=-.510) than general working experience (d=-.212). The median score in ACLS knowledge is low (5/10), despite its importance. Multiple linear regression reveals that ACLS has the greatest impact on the score. A small portion of doctors have attended an ACLS course (22%), but the majority of them would participate (89%).